A look at teaching in multi-years classrooms - Geralda Maria de Bem; Cicero Nilton Moreira da Silva (Universidade Federal do Norte do Tocantins, 2019)
When we approach the multi-years classrooms, we need relate them to the rural location, since this is the place in which there is the school organization practice under this structure and functioning, that is, showing in the same classroom, students of different age groups and cognitive levels. Although it is presented in others scenes, however, it is in the field that the identity of the multi-years classrooms is constituted, being its presence alive in the Brazilian educational scene. This article, however, aims at reflecting about this issue, using as methodological procedure the bibliographical research. Therefore, in order to allow a theoretical review about the theme, we will seek contributions in authors, such as Arroyo and Fernandes (1999), Tardif (2002), Santos and Moura (2010), Azevedo and Queiroz (2010), among others, who discuss the thematic at issue. In short, this work has showed us the need to deepen the reflection about the teaching at schools with multi-years classrooms and teaching knowledge that permeates pedagogical practice of teachers who teach this modality of teaching.